Entry guidance for high-L/D hypersonic vehicle based on drag-vs-energy profile. (December 2018) - Zhang, Wanqing; Chen, Wanchun; Yu, Wenbin
Abstract: To steer a hypersonic vehicle of high Lift-to-Drag ratio (L/D) safely and accurately, a new entry guidance is proposed based on drag-vs-energy profile. Over the rotating Earth, by assessing the nonlinear inertial forces reasonably, an accurate analytical glide-range formula is derived for formulaic drag profile. Then the reference drag-vs-energy profile is planned by utilizing the new formula in the entry corridor satisfying stress and thermal constraints. In order to closely track the reference profile, the Trajectory Damping Control Technique (TDCT) is adopted to suppress the underdamped, phugoid trajectory oscillations. The key to this technique is that the Analytical Formula of Flight-Path Angle for Steady Glide (AFFPASG) can maintain a high accuracy even if the vehicle deviates from the steady-glide condition greatly. This paper attempts to take a theoretical analysis on this interesting phenomenon though the expression of AFFPASG is complicated. By reviewing the derivation process of the AFFPASG carefully, we dig out its error sources and evaluate their influence on accuracy. As a conclusion, the fundamental cause of that key characteristic is that the Steady-Glide Flight-Path Angle (SGFPA) is the flight-path angle keeping the minimum change rate of the vertical component of the resultant of the external forces including the centrifugal force resulting from the Earth curvature, instead of the one making the vertical net force zero. Highlights: Accurate analytical glide range formulae for rotating Earth are proposed for reference drag profiles. A new steady-glide entry guidance based on the analytical formula is developed for high-L/D hypersonic vehicle. The accuracy and robustness of the key formula of the Trajectory Damping Control Technique (TDCT) is analyzed theoretically.